The Impact of Islamic Religious Education on Children's Worship Abilities at Home - Ade Imun Romadan; Dadan Sunandar; Mona Qonitah; Lailatul Fithriyah Azzakiyah; Muzakki Muzakki (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Islamic Religious Education plays a strategic role in shaping character, strengthening religious moderation, and supporting the spiritual and moral development of children from an early age in Indonesia. This study aims to analyse the influence of Islamic Religious Education on children's worship abilities and the formation of religious character in early childhood. The research employs a correlational quantitative design with a sample of 65 students. Data were collected via questionnaires administered to parents and analysed using SmartPLS, which included validity and reliability tests, as well as tests of the significance of relationships between variables. The results show that the implementation of Islamic Religious Education has a positive and significant effect on children's worship abilities, with an estimated influence of 0.386. An increase in the Islamic Religious Education Implementation (IIRE) has been proven to improve children's skills in worship practices, such as reading Iqra', performing salawat, azan, dhikr, and wudu, with a t-statistic value of 4.197 and a p-value of 0.000. Regular religious activities at school not only impart knowledge but also familiarise children with the practical aspects of worship. With a standard deviation of 0.092, children become more confident, skilled, and spiritually disciplined, resulting in a significant improvement in their worship abilities at home. The conclusion is that the implementation of Islamic Religious Education significantly enhances children's worship abilities, builds practical skills, spiritual discipline, and self-confidence from an early age.